GEOECOLOGICAL STATUS OF LOCAL TERRITORIES AS A PREREQUISITE FOR THE DEVELOPMENT OF RURAL UNITED TERRITORIAL COMMUNITIES OF THE WEST POLISSІA REGION - Lyko, Dariia; Mudrak, Oleksandr; Lyko, Serhii; Portukhaі Oksana; Мартинюк Vitalii; Zubkovуch Ivan; Yakuta, Olha (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The geoecological status of the territory of the Kozyn Rural United Territorial Community (RUTC) has been analyzed by the following indicators: the structure of the land fund, emissions of pollutants into the air, water use and drainage, solid household waste, the percentage of conservation of the territory. The agrochemical points of the most widespread agricultural produсtion groups of soils, according to which they belong to the V and VI groups and characterized by average quality, are considered. Cartographic models of forest and agricultural land, plowed land, the ratio of ecologically-stabilized lands (ESL) to anthrоpogenicallytransformed lands (ATL) have been constructed. A significant excess of ATL over ESL was found (87.99% / 12.01%), which confirms a very high level of transformation of landscape complexes. The coefficient of economic development of the territory is calculated, which indicates the critical geo-ecological state of the RUTC. According to the results of the SWOT analysis, the weaknesses of the ecological block of the sustainable development model of the Kozyn rural (RUTC) were identified, which included: high level of inclusion in the economic circulation of land resources, which threatens the balance of development of agroecosystems; high level of transformation of landscape complexes; a small percentage of forested areas; imperfect solid waste management system; lack of centralized cleaning of drainage systems; insufficient percentage of protected areas in accordance with the requirements of the European environmental legislation.